Reviewing generic innovation in the Lacedaimonion Politeia (Revista Archai, 2021)
This paper examines the generic structure and underpinnings of Xenophon's Lacedaimonion Politeia. The Lac. has frequently been regarded as a praise or defence of Sparta yet its rhetoric and narrative structure bear little resemblance to contemporary practices for composing encomia or defense speeches. Although this does not preclude an encomiastic or defensive purpose, an examination of the type of rhetoric Xenophon employs and the narrative patterns and structures in the work reveal different generic affiliations, showing that the Lac., like many of Xenophon’s other writings, is a hybrid work with features belonging to politeia- literature and philosophical enquiry. Further, careful examination, in particular, of the way Xenophon makes use of imaginary interlocutors (a feature of both types of writing) suggests that praise cannot have been the aim of this treatise.